2001
DOI: 10.1183/09031936.01.00078801
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intermittent hypercapnic hypoxia increases pulmonary arterial pressure and haematocrit in rats

Abstract: Chronic intermittent hypercapnic hypoxia increases pulmonary arterial pressure and haematocrit in rats. M. McGuire, A. Bradford. #ERS Journals Ltd 2001. ABSTRACT: Sleep-disordered breathing is associated with pulmonary hypertension and raised haematocrit. The multiple episodes of apnoea in this condition cause chronic intermittent hypoxia and hypercapnia but the effects of such blood gas changes on pulmonary pressure or haematocrit are unknown. The present investigation tests the hypothesis that chronic interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 37 publications
3
57
0
2
Order By: Relevance
“…How can the discrepancy between clinical observations and the results of recent animal studied showing development of PH after exposure to short repetitive episodes of hypoxia similar to those observed in patients with OSAS [11,12] be explained? Early studies on animal models demonstrated that short amounts of exposure, lasting only few hours per day, to hypoxia may imitate nocturnal desaturation in COPD patients which has also resulted in the development of permanent PH [25,26].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…How can the discrepancy between clinical observations and the results of recent animal studied showing development of PH after exposure to short repetitive episodes of hypoxia similar to those observed in patients with OSAS [11,12] be explained? Early studies on animal models demonstrated that short amounts of exposure, lasting only few hours per day, to hypoxia may imitate nocturnal desaturation in COPD patients which has also resulted in the development of permanent PH [25,26].…”
Section: Discussionmentioning
confidence: 96%
“…Recently, McGuire and Bradford [11] demonstrated the development of pulmonary hypertension in rats exposed to short bursts of hypoxia and hypercapnia imitating apnoeic episodes. Fagan [12] studied the effect of intermittent hypoxia in mice and also concluded that mice develop pulmonary hypertension in response to the repetitive hypoxia-reoxygenation.…”
Section: Introductionmentioning
confidence: 99%
“…Many biological and pathophysiological changes have been linked to intermittent hypoxia, i.e. alteration in baroreflex activity [91], increase in pulmonary arterial pressure and haematocrit [92], changes in heart structure and function [93], and an alteration in endothelial dependent vasodilation in cerebral and muscular arteries [94]. In addition, an increased response to endothelin (ET)-1 was also demonstrated [89], presumably almost exclusively mediated by ET-A receptors [95].…”
Section: Osa Intermittent Hypoxia and Cardiovascular And Metabolic Cmentioning
confidence: 99%
“…A variety of biological and pathophysiological changes have also been demonstrated, i.e. altered baroreflex activity [56], increased pulmonary arterial pressure and haematocrit [57], changes in heart structure and function [58], altered endothelium-dependent vasodilation in cerebral and muscular arteries [59], and an increased response to endothelin (ET)-1 [54], presumably mediated almost exclusively by ETA receptors [60]. During IH, both blood pressure (BP) and myocardial changes might be critically dependent upon ET-1.…”
Section: Cellular and Molecular Consequences Of Ihmentioning
confidence: 99%